89.8k views
2 votes
Given f(x) = 3x + 2 andg(x) = -2x - 4, find h(x) = f(x) - g(x).

User Holtwick
by
4.7k points

2 Answers

3 votes

All we need to do is plug in the equations for f(x) and g(x) into h(x)

Let's do it

f(x) = 3x + 2 and g(x) = -2x -4

h(x) = f(x) - g(x)

h(x) = (3x + 2) - (-2x - 4)

Combine like terms

(3x) - (-2x) → 3x + 2x → 5x

(+2) - (-4) → 2 + 4 → 6

Let's put them together

h(x) = 5x + 6

Hope I helped ! :)

User HaOx
by
4.9k points
2 votes

Answer:

h(x) = 5x+6

Explanation:

h(x) = f(x) - g(x)

h(x) = 3x+2 - (-2x-4)

h(x) = 3x+2 + 2x+4

h(x) = 5x+6

User Vlad Balmos
by
5.2k points